Modelo de gestão contábil e a parametrização nas prestações de contas em condomínios - Gaboardi, Rodolfo (2017)
The research proposes to demonstrate the importance of Accounting, as a management control, for the Condominium entities. The general objective of this work is to demonstrate the relevant role of accounting information for the management control of Condos, with the purpose of demonstrating the importance of accounting controls for the management of residential condominiums; demonstrate the models of condominial administration and quantify through research if the models and management applied are satisfactory. In order to reach the formulated objectives of the work, bibliographical research on the subject, books, dissertations and scientific articles was used, as well as, using the qualitative approach, through descriptive research, that is, a questionnaire related to management was carried out condominium and the accounting information given to the Trustees. The study was delimited through questionnaires sent to the Residential Condominium Trustees of the city of São Paulo, as they are responsible for the disclosure of the financial statements and also require this information for decision making. Finally, the research results were presented, contributing to the adequate use of Accounting as a tool for management control and accountability transparency